Design and optimization of lipid-modified poly(amidoamine) dendrimer coated iron oxide nanoparticles as probes for biomedical applications1. Issue 16 (28th April 2015) - Boni, A.; Bardi, G.; Bertero, A.; Cappello, V.; Emdin, M.; Flori, A.; Gemmi, M.; Innocenti, C.; Menichetti, L.; Sangregorio, C.; Villa, S.; Piazza, V.
<x xml:space="preserve">Abstract</x> Superparamagnetic iron oxide nanoparticles with a wide size range (2.6–14.1 nm) were synthesized and coated with the amphiphilic poly(amidoamine) PAMAM-C12 dendrimer.